In memoriam: Anthony Molyneux Meyers - Naicker, Saraladevi (African Journal of Nephrology, 2022)
Professor Anthony Molyneux Meyers, a pioneer in nephrology in South Africa and a past president of the African Association of Nephrology, died on 24 September 2022 at the age of 89.